2018
DOI: 10.1108/jd-02-2018-0033
|View full text |Cite
|
Sign up to set email alerts
|

Using electronic information resources to solve cultural translation problems

Abstract: Purpose. This study investigates the use of electronic information resources to solve cultural translation problems at different stages of acquisition of the translator's cultural competence. Design/methodology/approach. A process and product-oriented, cross-sectional, quasiexperimental study was conducted with 38 students with German as a second foreign language from the four years of the Bachelor's degree in Translation and Interpreting at Universitat Autònoma de Barcelona, and 10 professional translators. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
(47 reference statements)
1
16
0
Order By: Relevance
“…In his study, Howard (2010) explored that these search engines effectively reduced the increasing printed volumes and improved online access to information. Olalla-Soler (2018) investigated that the explosion of database-related information makes the search for information more effective and therefore users prefer online information resources. In this connection, Eyo (2014) researched that the published scientific work of researchers in international journals is of unprecedented importance for the evaluation of university performance and intellectual growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In his study, Howard (2010) explored that these search engines effectively reduced the increasing printed volumes and improved online access to information. Olalla-Soler (2018) investigated that the explosion of database-related information makes the search for information more effective and therefore users prefer online information resources. In this connection, Eyo (2014) researched that the published scientific work of researchers in international journals is of unprecedented importance for the evaluation of university performance and intellectual growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Zheng (2014) compared professional translators with novice translators and found that the former made a higher percentage of decisions using predominantly internal support than the latter. Olalla-Soler (2018) reports that, even when student translators already possessed knowledge of a problem, they preferred to double-check by consulting external resources, whereas professional translators tended to rely on their internalized knowledge. These findings can be explained with Pym’s (2015) model of risks and efforts in translation, which suggested that translators might devote different amounts of effort while encountering different levels of risk.…”
Section: Research Backgroundmentioning
confidence: 99%
“…In the field of translation studies, translators' research behaviour is still a relatively new area of study, with practically all investigations presenting generic data (e.g., by Cui & Zheng, 2020;Désilets et al, 2009;Enríquez Raído, 2014;Gough, 2017;Hirci, 2013;Hvelplund, 2017Hvelplund, , 2019Massey & Ehrensberger-Dow, 2011;Muller-Spitzer et al, 2012;Olalla-Soler, 2018;Pinto & Sales, 2007Pinto et al, 2014;Sales & Pinto, 2011;Shih, 2019;White et al, 2008;Zapata, 2016;). Some references to individual differences can be found in the studies investigating translation process (e.g., by Carl et al, 2011a;Dragsted & Carl, 2013;Heinstrom, 2003;Huang, 2018;Hubscher-Davidson, 2009;Lehka-Paul & Whyatt, 2016;Tirkkonen-Condit, 2005).…”
Section: Previous Studiesmentioning
confidence: 99%